2019
DOI: 10.4103/ija.ija_183_19
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea and its knowledge and attitude among Indian anaesthesiolgists – A survey study

Abstract: Background and Aims: Obstructive sleep apnoea (OSA) has an estimated prevalence of 2%–4% in adult population and is increasing. Most of these are detected late which is the cause for higher perioperative morbidity. This survey was aimed to seek the level of knowledge and attitude of Indian anaesthesiologists towards OSA. Methods: The OSA Knowledge and Attitude (OSAKA) questionnaire (23-statements) was distributed to the anaesthesiologists attending the difficult airway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The OSAKA was developed for educational needs assessment and evaluation research and has been widely used across multiple physician populations in at least 10 countries around the world. [34][35][36][37][38][39][40][41][42][43][44][45] To identify publications of studies reporting on dentists' and physicians' knowledge of OSA using the OSAKA, a search of the literature was conducted using PubMed and Google Scholar using the search terms, "obstructive sleep apnea knowledge and attitudes". Of the 129 papers published through April 30, 2020, a total of 12 unique, peer-reviewed, original research publications (in print or online ahead of print) reporting total OSA-knowledge scores from physician surveys were found.…”
Section: Physician Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The OSAKA was developed for educational needs assessment and evaluation research and has been widely used across multiple physician populations in at least 10 countries around the world. [34][35][36][37][38][39][40][41][42][43][44][45] To identify publications of studies reporting on dentists' and physicians' knowledge of OSA using the OSAKA, a search of the literature was conducted using PubMed and Google Scholar using the search terms, "obstructive sleep apnea knowledge and attitudes". Of the 129 papers published through April 30, 2020, a total of 12 unique, peer-reviewed, original research publications (in print or online ahead of print) reporting total OSA-knowledge scores from physician surveys were found.…”
Section: Physician Studiesmentioning
confidence: 99%
“…Of the 129 papers published through April 30, 2020, a total of 12 unique, peer-reviewed, original research publications (in print or online ahead of print) reporting total OSA-knowledge scores from physician surveys were found. [34][35][36][37][38][39][40][41][42][43][44][45] No peer-reviewed, published, dentist survey studies of OSA knowledge using the OSAKA Questionnaire were found. Nine of the 12 publications were eligible for inclusion in analysis of individual items, because scores for each item were published [34][35][36][37][38][39][40][41][42] or the authors [34][35][36][37][38][39][40][41][42][43][44][45][46] shared individual-item scores with the first author (personal communication emails: Dr. Navin Devaraj on March 8, 2020; 35 Dr. Sohan Solanki on March 15, 2020; 36 and Dr. Donna Jeffe on April 3, 2020.…”
Section: Physician Studiesmentioning
confidence: 99%
“…Studies measuring OSA knowledge using OSAKA questionnaire have yielded variable results where experienced doctors and specialists have scored higher and recent graduates or medical students have scored lower 11–14,17,18 . Given the relatively under‐developed and predominantly user‐pay health‐care system of Pakistan, studies from Ecuador, Nigeria and India are most relevant to our study 11,13,17,18 …”
Section: Discussionmentioning
confidence: 97%
“…Residents and primary care doctors scored better on the knowledge component of the OSAKA tool in a follow‐up study with a mean score of 10.8 and 10.0 out of 18, respectively. Solanki et al measured the knowledge of OSA amongst trainee and consultant anaesthesiologists and reported a mean score of 12.01 out of 18 18 . Given the fact that anaesthesiologists receive specialised training in airway management, a much higher score was expected in Solanki et al study.…”
Section: Discussionmentioning
confidence: 97%
“…Intermittently recorded RR is an estimated or 'spot' measurement,[ 7 ] may not accurately represent the dynamic nature of RR and the HCPs may not be able to timely detect obstructive apnoeic episodes. [ 8 ] The importance of dynamic continuous RR measurement may be particularly relevant to the use of modified early warning systems (MEWS) which are reliant on timely and accurate vital signs measurements. The additional feature of wireless monitoring device overcomes the bulkiness of standard monitoring systems, which could be useful in further improving the continuous monitoring of patients, especially in isolation room settings.…”
Section: Discussionmentioning
confidence: 99%